The Governing-Evaluation-Knowledge Nexus Swedish Higher Education as a Case - Segerholm, Christina; Hult, Agneta; Lindgren, Joakim; Rönnberg, Linda (Evaluating Education: Normative Systems and Institutional Practices, 2019)
This Open Access book analyses the interplay between governing, evaluation and knowledge with an empirical focus on Swedish higher education. It investigates the origins, logics, and mechanisms of evaluation and quality assurance reforms and their dynamic interactions with institutional, national and European policy contexts. The chapters report findings from extensive empirical studies that offer detailed insight into the work of governing in higher education, by giving voice to actors at various levels and positions including the ministry, national agency and University employees. Central themes include the influence of European policy, changing system designs, media relations and quality assurance enactments in University institutions. The book also explores the ways in which an emerging professional cadre, labelled qualocrats, enacts and mediates evaluation and quality assurance policy and practice. Taken together, the expanding evaluation machinery in Swedish higher education highlights the pivotal role of knowledge as a governing resource, and points to special features of evaluation as a particular form of practice that makes knowledge work for governing.